2017
DOI: 10.1590/1806-9282.63.10.837
|View full text |Cite
|
Sign up to set email alerts
|

Implications for public health of the religiosity-longevity relation

Abstract: ImplIcatIons for publIc health of the relIgIosIty-longevIty relatIon rev assoC med bras 2017; 63(10):837-841 837 POINT OF VIEWImplications for public health of the religiosity-longevity relation A growing body of scientific studies has demonstrated a consistently positive association between religious-spiritual (R/S) involvement and beneficial effects on physical health, culminating with increased longevity. This protective effect on the mortality risk is not only statistically significant but also clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Multiple researchers proposed that direct physiological pathways might also be involved [14,[17][18][19]. Religiosity/spirituality might lead to a reduction in heart rate or blood pressure [17,32,33].…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Multiple researchers proposed that direct physiological pathways might also be involved [14,[17][18][19]. Religiosity/spirituality might lead to a reduction in heart rate or blood pressure [17,32,33].…”
Section: Review Of Literaturementioning
confidence: 99%
“…During the past few decades, several studies suggested a positive association between religiosity/spirituality and benefits associated with the mental and physical health [14][15][16][17][18]. Koenig et al have defined spirituality as "the personal quest for understanding answers to ultimate questions about life, about meaning and about relationship to the sacred or transcendent, which may (or may not) lead to or arise from the development of religious rituals and the formation of community" [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a large number of theoretical and empirical studies have shown that religion can improve health and longevity . For example, a higher frequency in the participation of religious activities will lead to lower blood pressure and reduced smoking behavior .…”
Section: Introductionmentioning
confidence: 99%